ANALISIS PERFORMA DIAMOND BIT DAN CONE BIT DENGAN MENGGUNAKAN METODE SPECIFIC ENERGY DI LAPANGAN JS SUMUR P2 DAN Q5 PT. PERTAMINA ASSET 3 - Hasbullah, Andrea; Bungasalu, Benny Abraham; Mulyadi, Mulyadi (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2023)
The JS field in the North West Java Basin consists of 6 formations, namely Jatibarang, Talang Akar, Baturaja, Upper Cibulakan, Parigi, Cisubuh formations. The formation that is proven to have the potential to develop is the Middle Cibulakan formation. The formations have different hardness characteristics and certainly require different bits to penetrate the specified formation.From these indications, the performance of the drill bits used in the JS field will be analyzed, namely the P2 and Q5 wells. In the P2 well, the performance of the Diamond Bit drill bit at a depth of 0-2500 ft is analyzed. While the Q5 well uses a Roller Cone Bit drill bit at a depth of 0-3000ft. The method used is Specific energy.From the bit performance analysis, the rocks penetrated are from the softest, medium to hard. For Diamond Bit on runs 1-2 show a low value because the penetrated formation is still soft, on runs 3-5 begin to show an increase in SE value because the formation is medium. And on runs 6-8 show a high value because the formation has started to hard. As for the Roller Cone Bit in runs 1-2 shows a low value because the formation is relatively soft, there is an increase in runs 3-5 although there is a decrease in the 4th run due to formation incompactness. However, the 6-8 runs show an increase again because the penetrated formation is classified as hard. So it can be concluded that the rock formation factor can affect the performance of the drill bit.